2020
DOI: 10.1111/idh.12473
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of dental floss with ellipsoidal knots vs conventional dental floss for plaque removal: A split‐mouth randomized trial

Abstract: Objectives To compare clinical efficacy for plaque removal between dental floss with soft ellipsoidal knots and conventional floss. Materials and Methods We studied 33 university students (29 females and 4 males, 13 of them undergraduate/postgraduate students of dentistry), including regular and sporadic (less once/wk) users of dental floss, with interproximal spaces ≤1 mm, who used floss with and without knots in a randomized manner following a split‐mouth design. The Modified Navy Plaque Index (RMNPI) by Rus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…To prevent disease of teeth with prostheses, more thorough dental care and controlling methods are needed compared to normal teeth [25][26][27][28]. For example, plaque accumulation around the prosthesis and inappropriate oral health management can cause periodontal disease and secondary caries [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…To prevent disease of teeth with prostheses, more thorough dental care and controlling methods are needed compared to normal teeth [25][26][27][28]. For example, plaque accumulation around the prosthesis and inappropriate oral health management can cause periodontal disease and secondary caries [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…In order to prevent disease of teeth with prostheses, more thorough dental care and controlling methods are needed compared to normal teeth [19][20][21][22][23]. In addition, periodontal disease and secondary caries can easily occur due to plaque accumulation under the prosthesis and inappropriate oral health management [24,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The present study is a comparative study that compares the outcome of different oral hygiene measures. As shown in Figure 1, the participants included 150 systemically healthy male subjects, with age range (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Regarding bias, ascertainment and performance bias were avoided as all clinical parameters were recorded by the same clinician who was totally blinded about the oral hygiene measures that the participants were already using.…”
Section: Materials S and Me Thodsmentioning
confidence: 99%
“…In concordance with the current study, a study performed by who found that different types of dental floss result in a reduction of total and interdental plaque index in comparison with brushing only. 24 Although dental floss is not useful in reversing periodontal diseases, it has been stated by the European Federation of Periodontology that the use of dental floss may avoid the development of gingival inflammation and periodontal diseases. 25 The highest mean of GI was found in the teeth brushing group although there were no significant differences among groups these results agree with ) 26 who found no significant differences in gingival index between groups who used and not used manual dental floss.…”
Section: Dental Floss Group Mean ± Sdmentioning
confidence: 99%